(untitled) (Argos, 2024)
The word πέπλος (“peplos”), which typically names the tunic worn by women, is registered a total of eleven times in Euripides’ Hecuba. Taking into account the bipartite structure of this tragedy and the significance of clothing in the Ancient Greek world, this article intends to analyze the occurrences of this term in its contexts, with the hypothesis that the peploi conceal but at the same time reveal the nature of the female characters: Polyxena, the chorus of captive Trojan women and Hecuba, as well as they allow the transformation of the last two in each part of the play.